ADVANCING FABRIC MATERIAL DIGITALIZATION THROUGH PHOTOMETRIC STEREO RECONSTRUCTION - Hristozov, Atanas (Innovation in Woodworking Industry and Engineering design, 2024)
Photometric stereo reconstruction is a contemporary approach to digitizing fabric surfaces. By capturing multiple images of the surface illuminated from various angles and analyzing the resulting shadows, this method reconstructs the material's volume. It excels in capturing intricate texture details, particularly on surfaces with microscopic intricacies like fabric materials.